1996
DOI: 10.1103/physrevlett.77.334
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-Coupled Spin-Fluctuation Theory: Application to Fe, Co, and Ni

Abstract: Finite-temperature properties are modeled for the itinerant-electron ferromagnets Fe, Co, and Ni by employing a spin-fluctuation theory where the modes are coupled by interatomic exchange interactions. Our method is based on the density functional theory using the local density approximation. The latter yields all parameters derived from constrained ground-state properties of noncollinear spin configurations to calculate ab initio the Curie temperatures, the magnetic susceptibilities, and, furthermore, the hcp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(121 citation statements)
references
References 24 publications
11
110
0
Order By: Relevance
“…This means there is no way for the size of the Ni moments to respond to the energy cost of orientational disorder by reducing the exchange splitting. A number of authors have proposed ways to lift this constraint 3,11 . In both of these methods the parameters of the classical model were obtained by the use of the structure inverse method.…”
Section: Inclusion Of Longitudinal Fluctuationsmentioning
confidence: 99%
“…This means there is no way for the size of the Ni moments to respond to the energy cost of orientational disorder by reducing the exchange splitting. A number of authors have proposed ways to lift this constraint 3,11 . In both of these methods the parameters of the classical model were obtained by the use of the structure inverse method.…”
Section: Inclusion Of Longitudinal Fluctuationsmentioning
confidence: 99%
“…Other types of transverse fluctuations which are neglected in the two approximations, or longitudinal spin fluctuations which are totally neglected in the Heisenberg model, are more relevant. For an ab initio calculation of T c , therefore, the ab initio spin fluctuation theory of Uhl and Kübler 25 which encompasses both transverse and longitudinal fluctuations, is more appropriate, and first test calculations indeed yielded 26 ‫ץ‬T c /‫ץ‬pϽ0 when taking into account longitudinal fluctuations, and ‫ץ‬T c /‫ץ‬pϾ0 when neglecting them. Alternatively, Kakehashi 27 took both types of fluctuations into account by a variational approach to the degenerate-bands Hubbard model, and obtained for reasonable parameters of the model values for ‫ץ‬T c /‫ץ‬p which are larger in magnitude than our value but with a negative sign, again in disagreement with the experiment.…”
mentioning
confidence: 99%
“…However, electrons are still expected to be scattered by fluctuating local moments [18,19]. In previous supercell LB calculations [8] the local moment in fcc-Ni was used as an adjustable parameter, and it was found that agreement with experiment requires the local moment of about 0.35 µ B .…”
Section: Transition Metal Ferromagnets: Bcc-fe and Fcc-nimentioning
confidence: 99%
“…In fcc-Ni, the DLM moment collapses to zero while the moment in a real material is expected to persist due to longitudinal spin fluctuations. [18,19] In this case we employ the fixed-spin moment (FSM) approach [20] and treat the local magnetic moment as an adjustable parameter to recover the experimental value of the SDR [9]. In the case of hcp-Gd we used both the open-core and the LDA+U approaches [21].…”
Section: Formalism and Computational Detailsmentioning
confidence: 99%